Efficacy and safety of 1064-nm Nd:YAG laser in treatment of onychomycosis. (2nd January 2016) - Wanitphakdeedecha, Rungsima; Thanomkitti, Kanchalit; Bunyaratavej, Sumanas; Manuskiatti, Woraphong
Abstract: Background : Onychomycosis is a common nail disease, especially in older patients. Various treatment options are currently available for onychomycosis; however, their limitations include high failure rates, time-consuming nature, high cost and high risk of drug interactions. Previous studies on the treatment of dermatophyte onychomycosis with a long-pulsed 1064-nm Nd:YAG laser demonstrated excellent outcomes without severe side effects. Objective : To evaluate the efficacy and side effects of onychomycosis treatment with a long-pulsed 1064-nm Nd:YAG laser. Methods : Sixty-four onychomycotic nails (35 patients) were evaluated. The first treatment cycle involved treatment with a long-pulsed 1064-nm Nd:YAG laser in four sessions at 1-week intervals. A potassium hydroxide examination and fungal culture were performed every week during this treatment course and then at a 1-month follow-up visit. If either test was positive for a pathogenic organism, a second treatment cycle was performed. If the two tests produced negative results, each affected nail was followed up at 3- and 6-month visits after completion of the second treatment protocol. In cases of resistance (positive for a pathogenic organism after completion of the second treatment cycle), the onychomycotic nails were excluded from the study and treated by standard methods. Results : Of all 64 nails evaluated, 59 completed the first cycle of treatment and 24 (40.7%) demonstrated mycological clearance at the 1-month follow up. Thirty-five of the 59 nails (59.3%) were positive for a pathogenic organism and underwent a second treatment cycle. Upon completion of the second treatment cycle, 28 nails remained enrolled in the study, and the mycological test results were negative in nine of these (31.2%). For all nails that completed the first or second treatment cycle, the overall cure rates at the 1-, 3- and 6-month follow-up visits were 63.5, 57.7 and 51.9%, respectively. Side effects were mild and limited to erythema and swelling after the laser procedure. Conclusions : Long-pulsed 1064-nm Nd:YAG laser therapy is safe and effective for the treatment of onychomycosis. However, a larger sample and longer follow-up period are needed to confirm our findings.